I BELONG TO EVERYBODY AND I BELONG TO NOBODY’: A SOCIO-PRAGMATIC ANALYSIS OF PRESIDENT BUHARI’S INAUGURAL ADDRESS - Oyinkan, Medubi,; Fatima, Amuda, (IJRDO - Journal of Social Science and Humanities Research, 2017)
This paper examines President Buhari’s inaugural address of May 29, 2015. It aims to elucidate the meanings encoded in the inaugural speech and the functions they perform in an actual context of use. It uses the quote, ‘I belong to everybody and I belong to nobody’ as the anchor for a socio-pragmatic analysis of the speech. The paper attempts to elicit how President Buhari uses language to project his determination and commitment to transform the Nigerian polity. Using the speech act theory, context, politeness principle of face and relevant sociolinguistic factors, this paper also provides an insight into the main intention in the inaugural speech. The speaker uses contrasting situations and collective strategy to project the sociolinguistic variables in the speech. Thus, the socio-pragmatic analysis of the speech helps to reveal that the main intention of President Buhari is to seek for cooperation, teamwork, understanding and support from everyone in order to achieve true federalism and for national development and unity. The socio-pragmatic analysis also depicts the anchor utterance, ‘I belong to everybody and I belong to nobody’ as a true proposition of the speaker’s intent.